Composition and functional groups of epiedaphic ants (Hymenoptera: Formicidae) in irrigated agroecosystem and in nonagricultural areas - Hernández-Ruiz, Patricia; Castaño-Meneses, Gabriela; Cano-Santana, Zenón (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the species composition and functional groups of ants in nonagricultural (NA) and in irrigated areas (S, seasonal irrigation; P, irrigation with well water; W, irrigation with wastewater) in an arid agricultural region in central Mexico, throughout 2005 and 2006. A total of 52,358 ants belonging to 6 subfamilies, 21 genera and 39 species was collected using pitfall traps. The species best represented in all plots were: Forelius pruinosus, Pheidole obtusospinosa, Monomorium minimum and Dorymyrmex spp. NA plots recorded the highest density of ants. The highest values for diversity (H') and equitativity (J') were recorded in NA and P plots, while the lowest were recorded in W plots. Cluster analysis showed two different groups regarding species composition: NA-S and W-P. Functional groups recorded were: dominant Dolichoderinae, three species; subordinate Camponotini, five species; hot climate specialists, three species; tropical climate specialists, seven species; cold climate specialists, five species; cryptic species, one species; opportunists, six species; generalized Myrmicinae, nine species. Agricultural activity affects the structure of the ant community with epiedaphic forage, and the constant use of irrigation wastewater in conjunction with intense agricultural practices has negative effect upon species richness of epiedaphic ants.